Meningkatkan Aktivitas dan Hasil Belajar Muatan Matematika Menggunakan Kombinasi Model PBL, GI, dan Talking Stick pada Siswa Kelas V SDN Belitung Selatan 5 - Norhidayah; Herti Prastitasari (Jurnal Pendidikan Sosial Dan Konseling, 2024)
The problem in this study is the low activity and learning outcomes of mathematics students. The cause is one-way dominant learning and student difficulty in understanding mathematical concepts. Efforts made to overcome this problem is by using a combination of PBL, GI, and Talking Stick Models in learning. The purpose of this study is to describe the activities of teachers and analyze the improvement of student activity and learning outcomes. The approach used is a qualitative approach to the type of Class Action Research (PTK) during 4 meetings in Class V SDN Belitung Selatan 5 which amounted to 22 students. Types of data used are qualitative and quantitative data. The results of this study showed that the activity of teachers has increased, at the 1st meeting obtained a score of 28 with the category “Good” until at the 4th meeting obtained a score of 43 with the category “very good”. Student activity has increased, at meeting 1 reached 41% with the category “A small percentage of active students” until at meeting 4 reached 100% with the Category “All students are very active”. Learning outcomes have increased in every aspect of the category of “a small percentage of students complete " to "all students complete". At meetings 1 to 4 cognitive aspects increased from 36% to 100%, affective at meetings 1 to 4 increased from 41% to 100% and psychomotor at meetings 1 to 4 increased from 41% to 100%. So, based on the results of the study, it can be concluded that the combination of PBL, GI, and Talking Stick models can improve student activity and learning outcomes. The results of this study are expected to be used as a reference in using learning models that can improve students ' mathematical activities and learning outcomes.